ANALISIS PENERAPAN KONSEP ERGONOMI UNTUK MENDESAIN MESIN POTONG KULIT KERANG MUTIARA - I Wayan Joniarta; Made Wijana; I G.A.K. Chatur Adi W.A.; I Gede Bawa Susana; I Made Suartika (Energy, Materials and Product Design, 2022)
The application of the concept of ergonomics is carried out on seashell craft work facilities because the work facilities used are not in accordance with the principles and norms of ergonomics feasibility. The research objective is the redesign of cutting machines and work chairs based on various kinds of information related to human factors which include designing tools and work facilities that are more effective, safe, comfortable, healthy, and efficient (ENASE). Some of the ergonomic parameters that are used as references include aspects of anthropometry, human physical performance, effectiveness-efficiency, work productivity, and the subjectivity of complaints of body pain as a result of inappropriate positions and workloads. In this study, 1 unit of circular model of shell cutting machine was designed and 1 unit of chair / seat. With anthropometric measurements of employees and through ergonomic calculations using the 5th percentile, the dimensions of the work table (cutting table) were obtained, the size of the table height was 87, 9 cm long table 110 cm and table width 64.3 cm. Then the dimensions of the chair are also obtained as follows: seat base height 32.7 cm Chair base length 70.6 cm Chair base width 32.1 cm chair back height 56.8 cm cm, seat back width 44.5 cm After applying the principles of ergonomics, based on the results of the Nordic Body Map questionnaire, it was found that the application of ergonomic principles to work tools for clam shell workers resulted in a 128% decrease in musculoskeletal complaints. In addition to this, it also resulted in a decrease in fatigue levels of 103%. . This shows that the application of ergonomic principles has a positive impact on employees